Empowering Rural Women through Access to Credits in Kano State Region: The Role of Co-Operatives - Mohammed, Nuratu (American Journal of Humanities and Social Sciences, 2016)
Men and women not only have differing access toresources, gender based responsibilities which is seen by Falola (1996) as a sociological construction alsoresult in differences in the management and distribution of resources withinthe household and the community. The United Nations Development in 1993 coinedthe sustainable human development, the achievement of which depends on amongother factors accessibility of women to production resources and participationin cooperative organisations The study examined the role of co-operativesexpanding women’s access to credit facilities in some rural areas of Kano andJigawa states. Two peri- urban settlements –Dawanau and Dawakin Tofa in KanoState and Four rural areas Marke in Kano State and Furji, Acilafia and Gwiwawere selected for the study. A total of 200 female co-operative members drawn fromthe list of 669 selected co-operative members in the villages were selectedthrough a process of stratified random sampling while a total of 110 female noncooperative members and 110 males were selected through systematic random samplingtechnique. Data was gotten from thequestionnaire administered to the samples and from the focus group discussion, other sources was through the documents of the femalecooperative members gotten from the ministry of women affairs and women leadersin each study settlements. Information about the female non co-operativemembers’ and the male respondents was gotten from the village heads andconfirmed through the house to house enumeration of the villages. The datacollected was analysed using descriptive statistics, chi square, Logit modeland correlation statistical tests. The conclusion drawn from the study revealedsignificant difference in access to credits and income of female cooperativemembers and female non cooperative members. The logit model result show that membership ofcooperatives was influential in predicting access of women to credit sourcedfrom government and this was engineered through the activities of developmentofficers of the ministry of women affairs. It is recommended that women shouldbe encouraged to participate in viable cooperative organizations for them tobenefit in development programmes crucial for their socio economic empowerment.Key words: women, gender, rural, credits,co-operatives and empowerment.